Examining Traditional and Novel Validity Indicators from the Medical Symptom Validity Test Across Levels of Verbal and Visual Memory Impairment. (28th May 2021) - Cerny, Brian M; Resch, Zachary J; Rhoads, Tasha; Jennette, Kyle J; Singh, Palak G; Ovsiew, Gabriel P; Soble, Jason R
Abstract: Objective: This cross-sectional study examined accuracy of traditional Medical Symptom Validity Test (MSVT) validity indicators, including immediate recognition (IR), delayed recognition (DR), and consistency (CNS), as well as a novel indicator derived from the mean performance on IR, DR, and CNS across verbal, visual, and combined learning and memory impairment bands. Method: A sample of 180 adult outpatients was divided into valid ( n = 150) and invalid ( n = 30) groups based on results of four independent criterion performance validity tests. Verbal and visual learning and recall were classified as indicative of no impairment, mild impairment, or severe impairment based on performance on the Rey Auditory Verbal Learning Test and Brief Visuospatial Memory Test-Revised, respectively. Results: In general, individual MSVT subtests were able to accurately classify performance as valid or invalid, even in the context of severe learning and memory deficits. However, as verbal and visual memory impairment increased, optimal MSVT cut-scores diverged from manual-specified cutoffs such that DR and CNS required cut-scores to be lowered to maintain adequate specificity. By contrast, the newly proposed scoring algorithm generally showed more robust psychometric properties across the memory impairment bands. Conclusions: The mean performance index, a novel scoring algorithm using the mean of the three primary MSVT subtests, may be a more robust validity indicator than the individual MSVT subtests in the context of bona fide memory impairment.